2015
DOI: 10.4103/1119-3077.158962
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective review of intensive care management of organophosphate insecticide poisoning: Single center experience

Abstract: Background: Organophosphate (OP) compounds are used as insecticides. Given the widespread availability and use of these chemicals, OP poisoning is quite common following either accidental or intentional exposures. Immediate intensive care management can save lives in these patients. We aimed to investigate intensive care management provided to OP poisoning patients in a tertiary care hospital in Turkey. Subjects and Methods: This was a retrospective chart review of 62 patients, admitted to the Intensive Care U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 32 publications
5
25
0
Order By: Relevance
“…3,37,38 This might be explained by the fact that atropine was prescribed in a very low dose for a short time with oxime therapy not prescribed to all patients and inadequate supportive care. Studies conducted after the year of 2000 have consistently shown mortality rates below 15%.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,37,38 This might be explained by the fact that atropine was prescribed in a very low dose for a short time with oxime therapy not prescribed to all patients and inadequate supportive care. Studies conducted after the year of 2000 have consistently shown mortality rates below 15%.…”
mentioning
confidence: 99%
“…Studies conducted after the year of 2000 have consistently shown mortality rates below 15%. 37,39 This can be explained by universal provision of continuous high dose atropine, consistent use of pralidoxime and better access to supportive therapy such as ICU care, ventilator support and respiratory therapy etc. In our study, the mortality was 17.34% (56 of the 323 cases) and 124 (38.41%) patients had to be ventilated.…”
mentioning
confidence: 99%
“…OP poisoning commonly occurs following ingestion, inhalation, and absorption of OP compounds4, 5 The most common mechanism of ototoxicity associated with OP poisoning is production of reactive oxygen species (ROS) 6 . OPs also affect acetylcholinesterase, whose function is to hydrolyze acetylcholine that most important neurotransmitter in the central and peripheral nervous systems 1, 2, 5…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of OP poisoning was based on information taken either from the patient or their family about the agent involved in the exposure. We confirmed the diagnosis of OP poisoning by measuring plasma cholinesterase (ChE) levels [8]. ChE levels were determined using an Olympus U2700 spectrophotometric chemistry analyzer (Beckman Coulter, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%